DINAMIKA BRAND SWITCHING: PERAN VARIETY SEEKING DAN ELECTRONIC WORD OF MOUTH DALAM PERUBAHAN PREFERENSI KONSUMEN OTOMOTIF DI INDONESIA - Mulyadi , Mulyadi; Muchsin , Muchsin; Ariska, Emalia; Yusuf, M.; Zalikha , Zalikha (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Brand Switching is a consumer behavior in which individuals shift from one brand to another when purchasing products within the same category. This means that consumers who were previously loyal to a particular brand decide to try or switch to a competing brand. This study aims to analyze the influence of variety seeking and electronic word of mouth (eWOM) on brand switching in Indonesia’s automotive industry, particularly marked by the shift from Japanese to Chinese brands. The phenomenon of brand switching has become increasingly common in the digital era, driven by consumers’ desire for variety and information obtained through online reviews. Variety seeking, based on the Optimal Stimulation Level (OSL) theory and novelty seeking, reflects the consumer's desire for new experiences. Meanwhile, eWOM, grounded in social proof and information adoption theories, shapes perceptions through online reviews. This quantitative study utilized a questionnaire distributed to 100 respondents who had switched car brands. Data were collected using a Likert scale of 1 to 5. The data analysis employed Multiple Linear Regression and was processed using SPSS version 24. The hypothesis testing revealed that variety seeking has a significant negative effect, eWOM has a significant positive effect, and both variables simultaneously have a significant positive effect on brand switching. Educated Indonesian consumers tend to consider value for money, innovation, and design when making brand-switching decisions. Companies need to leverage eWOM, enhance innovation, and understand consumer preferences to maintain market position and customer loyalty..